Improving the Monitoring of Implementation of the State Strategy for Regional Development in Ukraine - Stolietova, I. G. (Statistics of Ukraine, 2017)
The article is devoted to analysis of the specifics involved in implementing the State Strategy for Regional Development in Ukraine, and monitoring of its implementation. Methodological, organizational and economic recommendations on improvements of the regional development strategy formulation in the context of decentralization and the increasing importance of territorial and administrative setting in Ukraine are elaborated. The specifics involved in elaboration and implementation of the State Strategy for Regional Development in Ukraine till the year of 2020 are analyzed from the perspective of the strategic goals included in it: (і) enhancement of the regions’ competitiveness; (ii) territorial socio-economic integration and spatial development; (iii) effective public administration of regional development. A review of existing theoretical approaches to studying socio-economic development of regions is made, with outlining the existing drawbacks in monitoring. The emphasis is made on improvements in the system for assessment of the effectiveness of the achievement of goals and objectives of the regional development strategy, which will enable to make the decision making process in this field better grounded and improve control over its implementation It is argued that the system of statistical indicators needs to be constructed by the principle of consistency and informativeness, meaning that it has to be complete and capable to assess the development of Ukrainian regions in conformity with the fundamental provisions of regional policy The statistical tools selected and formed in timely and adequate manner have critical importance for practical implementation of the regional policy provisions. It follows that the statistical indicators have to be systematized in a way to be capable for assessing quantitative and qualitative specifics of macroeconomic and regional development. The system of indicators for assessment of the Strategy goals is formed, which expected estimates are targets of its implementation. It covers the indicators designed to assess the achievement of a result (such as number of finished projects), characterize the qualitative conditions of the regulated object (number of small enterprises per 10 thousand of the population), and the effectiveness of resource utilization (energy capacity). Also, the conceptual areas for improvement of the system for assessment of the effectiveness of the achievement of goals and objectives of the State Strategy for Regional Development are formulated.